2016
DOI: 10.1111/aspp.12261
|View full text |Cite
|
Sign up to set email alerts
|

What Drives Young People Into Opposition Parties Under Hybrid Regimes? A Comparison of Hong Kong and Singapore

Abstract: Research on youth participation in opposition parties under hybrid regimes is limited. This article explores and compares the contextual factors influencing young people to join opposition parties in the hybrid regimes of Hong Kong and Singapore. Based on life history interviews with 19 young opposition party members between the ages of 18 and 29 in both polities, this study identified seven significant factors. They are the characteristics of the opposition parties themselves, significant political events, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The rise of political activism is also signified by young adults' awareness of political values and rights, an increasing willingness to challenge the political authority and mainstream social and political values, and the use of radical tactics (Lam, 2018). Ng (2016) further showed that political events and the media are particularly important influences in young people's decisions to join opposition parties in flawed democracies such as Hong Kong. European research suggests that users of digital media and participants in collective protests also appear more willing to cast a protest vote (Mosca and Quaranta, 2017), particularly if they are dissatisfied with specific policy issues (Birch and Dennison, 2019).…”
Section: Youth Political Participation In Hong Kongmentioning
confidence: 99%
“…The rise of political activism is also signified by young adults' awareness of political values and rights, an increasing willingness to challenge the political authority and mainstream social and political values, and the use of radical tactics (Lam, 2018). Ng (2016) further showed that political events and the media are particularly important influences in young people's decisions to join opposition parties in flawed democracies such as Hong Kong. European research suggests that users of digital media and participants in collective protests also appear more willing to cast a protest vote (Mosca and Quaranta, 2017), particularly if they are dissatisfied with specific policy issues (Birch and Dennison, 2019).…”
Section: Youth Political Participation In Hong Kongmentioning
confidence: 99%
“…On the one hand, civic liberties are generally enjoyed by Hong Kong citizens, such as the freedom of speech and demonstrations. On the other, only half of the seats in the Legislative Council are directly elected by Hong Kong citizens through election as "geographical constituency"; therefore the opposition parties cannot win the majority power over the pro-China and pro-establishment parties (Cheng, 2016;Ng, 2016). Although electoral democracy is partially practised, the real power of governance is centralised in the hands of bureaucrats, economic elites and pro-government parties.…”
Section: Changing Youth Narratives and Policies Under The Hksar's Hybrid Regimementioning
confidence: 99%
“…It is revealed that the majority of young people are "disengaged individuals" whilst the "critical citizens" constitute the least. Moreover, the driving forces underlying young activism are diverse, which is subject to the influences of political events, the public and social media, and education experiences (Ng, 2016). Hence, the landscape of youth politics is anything but straightforward.…”
Section: New Ideas and Discourses For The Reconstruction Of Youth Policiesmentioning
confidence: 99%